Preservasi preventif arsip dinamis inaktif di Record Center Fakultas Ilmu Sosial dan Ilmu Politik Universitas Padjadjaran - Hikmatiara Abrori; Sukaesih Sukaesih; Lusi Romaddyniah Sujana (IJAL (Indonesian Journal of Academic Librarianship), 2023)
Archives are records that contain events and scientific knowledge. Archives are divided into two based on their function, namely dynamic archives and static archives. In its management, there are factors that can damage archives, so preventive preservation is needed so that archives can be used intact and for a long time. The Record Center as a place for managing inactive dynamic archives needs to carry out preventive preservation. This preventive preservation research uses descriptive qualitative methods with data collection methods in the form of observation, interviews, and literature study. Based on data obtained in the field, factors that can damage archives include physical, biological, and storage errors. To minimize the occurrence of damage caused by these factors, it is necessary to carry out camperization efforts, physical maintenance of archives, improvement of the quality of human resources, appropriate infrastructure, and adequate storage space.